COMPARATIVE ANALYSIS OF UNMET NEED SERVICES IN HEALTH IN INDONESIA IN 2020 AND 2023 - Hanipah, Rahmi Mughni; Marina, Sulis; Faisal, M Denis; Hajar, Siti (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2024)
Data from the Central Statistics Agency (BPS) shows that the percentage of unmet need for health services in Indonesia decreased from 6.09% in 2020 to 5.22% in 2023, with a decrease of 0.87 percentage points. Unmet need refers to an unmet need for health services, caused by factors of accessibility, availability, cost, or awareness. This study aims to identify changes in the availability and accessibility of health services during this period. The results show that there is a significant gap between the western provinces (Java and Sumatra), which have improved access and quality of health services, and the eastern provinces (Papua and Maluku), which still lack medical facilities and personnel. 2023 shows an increase in the number of medical personnel in urban areas, but uneven distribution is still a problem, especially in rural and remote areas. This study uses a quantitative method with an independent t-test. In conclusion, despite the overall decline in unmet demand, the gap between urban and rural areas and between western and eastern parts of Indonesia remains significant.